The Transport manager's & operator's handbook 1995 - Lowe, David 1936- (Kogan page, 1995)
The 25th edition of this book is the definitive guide to the UK road transport industry. It provides transport managers, fleet operators and drivers with an authoritative and comprehensive guide to the rules, regulations, and best practice of road freight operations.